2022
DOI: 10.1158/1538-7445.am2022-240
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 240: MERTK inhibition induces an anti-leukemia dendritic cell - T cell axis while TYRO3 inhibition protects through a separate mechanism

Abstract: The TAM family receptor tyrosine kinases TYRO3, AXL and MERTK are potential therapeutic targets in a variety of cancers. In previous studies, inhibition of MERTK decreased PD-1 checkpoint proteins in the leukemia microenvironment and prolonged survival in a syngeneic BCR-ABL+/Arf-/- B-cell acute leukemia model, implicating MERTK as a promising immune-oncology target in leukemia. Strikingly, Mertk-/- mice were largely protected from leukemia. In our current studies, Tyro3-/- almost completely prevented developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Further studies have demonstrated these findings with Mertk −/− mice and MERTK small-molecule inhibitors. Further, the mechanism of this anti-leukemia response was shown to be due, at least in part, to a T-cell/dendritic cell interaction in the bone marrow microenvironment [ 40 ]. While beyond the scope of this project, we hypothesize that MERTK plays a similar role in the leukemia microenvironment in T-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated these findings with Mertk −/− mice and MERTK small-molecule inhibitors. Further, the mechanism of this anti-leukemia response was shown to be due, at least in part, to a T-cell/dendritic cell interaction in the bone marrow microenvironment [ 40 ]. While beyond the scope of this project, we hypothesize that MERTK plays a similar role in the leukemia microenvironment in T-ALL.…”
Section: Discussionmentioning
confidence: 99%